Clinical profile, risk, and critical factors and the application of the "path toward intended violence" model in the case of mass shooter Dylann Roof. Issue 6 (3rd June 2019) - Allely, C. S.; Faccini, L.
ABSTRACT: A threat assessment perspective, namely the Path toward Intended Violence, was applied in the case of the mass shooting perpetrated by Dylann Roof on June 17, 2015 at an Emanuel African Methodist Episcopal Church in Charleston, South Carolina. This perspective is important since it attempts to build on accounts regarding how he progressed toward his mass shooting, beyond the information presented in the forensic evaluations already available. The Path toward Intended Violence was found to be a critical and proximal factor for the mass shooting. This suggested finding is also consistent for other individuals, who were diagnosed with an autism spectrum disorder (ASD), as well as neurotypical individuals, who have engaged in a mass shooting. The Path toward Intended Violence is also discussed as a potential way forward toward trying to identify individuals who may be more vulnerable and at-risk, so that appropriate interventions and supports can be put in place in order that such extreme violence can be prevented.